2014 IEEE 6th International Conference on Adaptive Science &Amp; Technology (ICAST) 2014
DOI: 10.1109/icastech.2014.7068069
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of non-preemptive priority with application to cloud E-marketplaces

Abstract: The increase in the level of awareness by consumers about the Cloud E-marketplaces has brought rapid growth in these competitive markets. As the markets grow, most providers are implementing different service offerings based on consumers' demand. One major challenge which has not been fully discussed in these markets is the performance impact of these offerings on consumers'. The goal of this research is to model a typical cloud marketplace and evaluate the performance impact on consumers' waiting time. To add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Akingbesote et al modeled a typical cloud E‐marketplace under a non‐preemptive policy and evaluated the performance impact on consumer waiting time. They found that as the server utilization became high, the performance of their model based on waiting time was 80% better than the conventional nonpriority model.…”
Section: Primary Studies and Classification Schemesmentioning
confidence: 99%
“…Akingbesote et al modeled a typical cloud E‐marketplace under a non‐preemptive policy and evaluated the performance impact on consumer waiting time. They found that as the server utilization became high, the performance of their model based on waiting time was 80% better than the conventional nonpriority model.…”
Section: Primary Studies and Classification Schemesmentioning
confidence: 99%
“…Several works have been done which ranges from GUI-SET's implementation [18][19][20] to its performance evaluation [17,21,22] and security [15,16,23] as well as the Pricing strategy to be used on the platform [14]. However, little research has been conducted in relation to providing an optimally satisfactory service especially in the newly integrated ad hoc model system.…”
Section: Introductionmentioning
confidence: 99%